2021
DOI: 10.3390/genes12081170
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Identifies 12 Loci Associated with Body Weight at Age 8 Weeks in Korean Native Chickens

Abstract: Meat from Korean native chickens (KNCs) has high consumer demand; however, slow growth performance and high variation in body weight (BW) of KNCs remain an issue. Genome-wide association study (GWAS) is a powerful method to identify quantitative trait-associated genomic loci. A GWAS, based on a large-scale KNC population, is needed to identify underlying genetic mechanisms related to its growth traits. To identify BW-associated genomic regions, we performed a GWAS using the chicken 60K single nucleotide polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 50 publications
0
20
0
1
Order By: Relevance
“…The other gene, LDB2 has previously been reported as a candidate gene for body size and carcass traits in ducks ). The KCNIP4 gene, a member of potassium channelinteracting proteins has extensive physiological functions and insulin secretion was identified as an important QTL region associated with growth traits in chickens (Cha et al 2021). SLIT2 has also been reported to be strongly associated with back yield, feet weight, fat and muscle weight traits in chickens (Cha et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The other gene, LDB2 has previously been reported as a candidate gene for body size and carcass traits in ducks ). The KCNIP4 gene, a member of potassium channelinteracting proteins has extensive physiological functions and insulin secretion was identified as an important QTL region associated with growth traits in chickens (Cha et al 2021). SLIT2 has also been reported to be strongly associated with back yield, feet weight, fat and muscle weight traits in chickens (Cha et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The availability of genome-wide single nucleotide polymorphism (SNP) and copy number variant (CNV) panels has made genomic prediction possible for a broad range of livestock [ 16 , 17 ]. In the past several years, genome-wide association studies (GWAS) have identified an increasing number of potential markers associated with phenotypes of interest, including weight, plumage color [ 18 , 19 , 20 , 21 ], disease [ 22 , 23 , 24 ], and other economically important traits [ 25 , 26 ], thereby contributing to an extensive understanding of traits biology and providing a list of positional candidate genes for quantitative traits in poultry and livestock. Meanwhile, the GWAS has also revealed candidate sites and genes for meat quality, which is a critical economic trait for livestock and poultry species.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, in a study that was part of the Genome-Wide Association Study (GWAS) with a 60K single nucleotide polymorphism (SNP) chip, 12 significant SNPs for body weight at eight weeks of age were observed in Korean native chickens (KNCs). These can be used as selection markers for body weight [6]. Similarly, another study investigated the selection signatures between Korean native chicken and commercial chicken breeds using 600K SNP chip data [7].…”
mentioning
confidence: 99%